2008
DOI: 10.5194/hess-12-371-2008
|View full text |Cite
|
Sign up to set email alerts
|

Climate control on sulphate and nitrate concentrations in alpine streams of Northern Italy along a nitrogen saturation gradient

Abstract: Abstract. The role of meteorology, hydrology and atmospheric deposition on the temporal pattern of SO 4 and NO 3 concentrations was investigated for three streams draining alpine catchments in Northern Italy.The study sites lie on a gradient of atmospheric fluxes of SO 4 and NO 3 (from about 50 to 80 meq m −2 y −1 , and from 40 to 90 meq m −2 y −1 , respectively). As a consequence of the increasing N input, the three catchments are also representative of aggrading levels of N saturation. Different methods of s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 39 publications
3
14
0
Order By: Relevance
“…Nitrogen release from forest soil (a symptom of soil N saturation, e.g. Dise & Wright, 1995) was already detected in previous studies carried out at some of our plots (Mosello et al, 2002;Rogora et al, 2008). A year-round release of NO 3 -from the watersheds of five of the plots considered in this paper, and high level of N saturation according to the Stoddard & Traaen (1995) criteria were reported for the plot PIE1.…”
Section: Accepted Articlesupporting
confidence: 74%
“…Nitrogen release from forest soil (a symptom of soil N saturation, e.g. Dise & Wright, 1995) was already detected in previous studies carried out at some of our plots (Mosello et al, 2002;Rogora et al, 2008). A year-round release of NO 3 -from the watersheds of five of the plots considered in this paper, and high level of N saturation according to the Stoddard & Traaen (1995) criteria were reported for the plot PIE1.…”
Section: Accepted Articlesupporting
confidence: 74%
“…The fluxes reported for European Alpine sites at elevation above 2000 m a.s.l. are between 0.5-3 kg N ha −1 yr −1 , but at lower altitude sites these rates greatly increase (Hiltbrunner et al, 2005;Rogora et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In April, there is a sharp decline in the water conductivity, which is related to the dilution with low-mineralized water from melting snow cover. As for nutrients (NH 4 + and NO 3 − ) in all sampling sites, it was confirmed that the highest concentrations occur in the beginning of snowmelt period (March, April), when the nitrogen compounds are leached out of the snow cover and soil (Rogora et al 2008;Holko et al 2006). On the other hand, during the growing period (June-September), the concentrations of these ions decrease, which is associated with assimilating them by plants (Campbell et al 2000;Clark et al 2004).…”
Section: Resultsmentioning
confidence: 77%